2018
DOI: 10.5334/jpl.189
|View full text |Cite
|
Sign up to set email alerts
|

The Acquisition Path of [w]-final Plurals in Brazilian Portuguese

Abstract: The plural of Brazilian Portuguese [w]-final nouns includes an alternation with [j], but the change is partially blocked in monosyllables and following a tense vowel (Becker et al. 2017). In this paper, we present a nonce word study with 115 children ages 7-13 and 43 adults, all participants from the state of São Paulo, showing that blocking in monosyllables is acquired earlier than blocking by tense vowels. We claim that sensitivity to monosyllabicity and vowel tenseness are both due to universal phonological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
22

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 20 publications
0
6
0
22
Order By: Relevance
“…While written with graphemes corresponding to non-high pretonic vowels, words like these are more frequently produced with pretonic high vowels [i] or [u], and show no alternations of [e ∼ i] or [o ∼ u] in this position. It is therefore very likely that BP speakers have stored these words with high pretonic vowels in their mental lexicon (showing a mismatch between orthography and underlying representation), and do not apply an active process of height harmony (see Becker, Nevins, Sandalo, and Rizzato (2018) who make a similar point with respect to [w ∼ j] plural alternations in BP). Our present study showed that for nonce words with the same orthographic presentation of pretonic vowels as the one found in the real words of earlier experimental studies, height harmony does not occur.…”
Section: Summary and General Discussionmentioning
confidence: 99%
“…While written with graphemes corresponding to non-high pretonic vowels, words like these are more frequently produced with pretonic high vowels [i] or [u], and show no alternations of [e ∼ i] or [o ∼ u] in this position. It is therefore very likely that BP speakers have stored these words with high pretonic vowels in their mental lexicon (showing a mismatch between orthography and underlying representation), and do not apply an active process of height harmony (see Becker, Nevins, Sandalo, and Rizzato (2018) who make a similar point with respect to [w ∼ j] plural alternations in BP). Our present study showed that for nonce words with the same orthographic presentation of pretonic vowels as the one found in the real words of earlier experimental studies, height harmony does not occur.…”
Section: Summary and General Discussionmentioning
confidence: 99%
“…Em contraste está a alternativa de se lexicalizar o morfema, mais do que sua base, assumindo-se, se não alomorfia propriamente dita, a hipótese de subléxicos, ativados por restrições fonológicas ou de outra natureza, inclusive extralinguística. É, por exemplo, a análise assumida por Becker et al (2018) e Rizzatto (2018), para o tratamento de plurais de palavras fechadas foneticamente por Vw, ou por Abaurre Gnerre (1983), para o tratamento de plurais de palavras fechadas por ditongo nasal.…”
Section: Alomorfia Produtividade E Plurais Irregulares Do Pbunclassified
“…A alternância dos expoentes fonológicos do plural de ditongos orais e nasais foi avaliada na perspectiva de sua produtividade em contextos fonológicos e morfológicos específicos por Huback (2010aHuback ( , 2010b, Cristófaro-Silva (2012), Becker et al (2018), Rizzato (2018), Gomes, Prado e Amaral (2021, no prelo), entre outros autores. Nesta seção apresentamos algumas das principais ideias desses textos em versão resumida.…”
Section: Estudos Sobre a Produtividade De Plurais Irregulares Em Pbunclassified
See 1 more Smart Citation
“…We appeal to the findings of Smith (2005) that the initial position is one that requires prominence-boosting for the psycholinguistic purposes of lexical access and word-recognition, in addition to potentially for reasons of speech planning by the speaker. For phonologically-based studies of the importance of the initial syllable, see Beckman (1998) and Becker et al (2018), among many others.…”
Section: Prominence-demanding Positions In Brazilian Portuguesementioning
confidence: 99%